2017
DOI: 10.1080/14728222.2017.1281250
|View full text |Cite
|
Sign up to set email alerts
|

Reactive nitrogen species as therapeutic targets for autophagy: implication for ischemic stroke

Abstract: Roles of autophagy/mitophagy activation in ischemic stroke remain controversial. To elucidate potential reasons, we analyze the factors responsible for divergent results in literatures. Reactive nitrogen species (RNS) are important cytotoxic factors in ischemic stroke. Herein, we particularly discuss the roles played by RNS in autophagy/mitophagy and ischemic brain injury. Areas covered: Following factors should be considered in the studies on autophagy/mitophagy in ischemic stroke: (1) Protocols for administr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 177 publications
0
20
0
Order By: Relevance
“…Recent reports also suggest a possible role for autophagy, being presumably regulated under diverse pathological conditions including stroke. Yet, the precise role of stroke-associated autophagy is elusive with autophagy being a double-edged sword that can be either protective or harmful [50]. Autophagy, however, appears to be of no concern in CCL11-aggravated ischemic brain injury of adult mice.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports also suggest a possible role for autophagy, being presumably regulated under diverse pathological conditions including stroke. Yet, the precise role of stroke-associated autophagy is elusive with autophagy being a double-edged sword that can be either protective or harmful [50]. Autophagy, however, appears to be of no concern in CCL11-aggravated ischemic brain injury of adult mice.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly for ischemic brain injury, we concluded that the interaction of RNS, Cav-1 and MMPs could form a positive feedback loop, amplifying the impact of RNS in BBB disruption and ischemic brain injury ( Figure 1 ). Therefore, targeting the RNS/Cav-1/MMP pathway is a promising therapeutic strategy for protecting against cerebral ischemia-reperfusion injury 28 , 108 , 123 .…”
Section: Role Of Caveolin-1 In Acute Ischemic Brain Injurymentioning
confidence: 99%
“…PINK1/Parkin-mediated mitophagy is activated in brain damage induced by ischemia stroke; however, the underlying function is unclear [162]. Although the function of mitophagy is still unclear in stroke, it is generally accepted that the degree of mitophagy is the determinant during stroke, and physiological levels can be beneficial, while excessive or inadequate levels could be deleterious [30,163].…”
Section: Strokementioning
confidence: 99%